Chinese and South Asian ethnicity, immigration status, and clinical cancer outcomes in the Ontario Cancer System. Issue 7 (9th January 2018) - Stevenson, James K.R.; Cheung, Matthew C.; Earle, Craig C.; Fischer, Hadas D.; Camacho, Ximena; Saskin, Refik; Shah, Baiju R.; Austin, Peter C.; Singh, Simron
Abstract : BACKGROUND: In the United States, certain minority groups have been shown to have inferior cancer outcomes compared with the white majority population. However, to the authors' knowledge, the majority of research has not separated ethnicity from immigration status. The objective of the current study was to determine the impact of ethnicity, independent of immigration status, on cancer outcomes in Chinese and South Asian populations in Ontario, Canada. METHODS: The authors conducted a population‐based retrospective cohort study using administrative databases in Ontario, Canada. Incident cancer cases were captured in Canadian‐born Chinese and South Asian individuals, Chinese and South Asian immigrants, and the general Ontario reference population (non‐Chinese/non‐South Asian and non‐immigrant) between 2000 and 2012. Subjects were followed until death (all‐cause and cancer‐specific), and Cox proportional hazard models were used to estimate the impact of Chinese and South Asian ethnicity on cancer outcomes after adjusting for explanatory variables. RESULTS: A total of 423, 678 cancer cases were identified; at total of 6631 cases were identified in Canadian‐born Chinese individuals and 2752 cases in Canadian‐born South Asian individuals. After adjustment, the rate of all‐cause mortality was lower for Canadian‐born Chinese (hazard ratio [HR], 0.829; 95% confidence interval [95% CI], 0.795‐0.865), Canadian‐born South Asian (HR, 0.856; 95% CI, 0.797‐0.919), and Chinese immigrant (recent immigrant: HR, 0.661 [95% CI, 0.610‐0.716] and non‐recent immigrant: HR, 0.853 [95% CI, 0.803‐0.906]) populations compared with the general Ontario population. A similar effect was found for cancer‐specific mortality. CONCLUSIONS: Chinese and South Asian ethnic groups appear to have lower cancer mortalities compared with the general Ontario population. After removing the well‐documented protective effect of immigration, Chinese and South Asian ethnicities were found to be associated with a cancer survival advantage in Ontario, Canada. Cancer 2018;124:1473‐82 . © 2018 American Cancer Society . Abstract : Chinese and South Asian ethnic groups have lower cancer mortality compared with the general (non‐Chinese/non‐South Asian and nonimmigrant) Ontario population. After removing the well‐documented protective effect of immigration, Chinese and South Asian ethnicities appear to be associated with a cancer survival advantage in Ontario, Canada.